2019
DOI: 10.22159/ijap.2019.v11s5.t0028
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Celery Leaves (Apium Graveolens L.) Formulated in Toothpaste Against Streptococcus Mutans

Abstract: Objective: The objective of this research was to determine the antibacterial activity of the toothpaste from an extract of celery leaves on Streptococcusmutans.Methods: The toothpaste was formulated with various concentrations of celery leaves, F1 with concentration of extract (6.25%), F2 (12.5%), andF3 (25%). Each formula was tested the physical characteristics and antibacterial activity toward S. mutans. The antibacterial activity was determinedby the agar well diffusion method using brain heart infusion aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Regarding Apium graveolens, Genatrika et al 4 tried to utilize its extract as toothpaste to inhibit Streptococcus mutans and it showed significant antibacterial activity against these bacteria, moreover, they showed that it has a protective or disease preventive antibacterial activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding Apium graveolens, Genatrika et al 4 tried to utilize its extract as toothpaste to inhibit Streptococcus mutans and it showed significant antibacterial activity against these bacteria, moreover, they showed that it has a protective or disease preventive antibacterial activities.…”
Section: Discussionmentioning
confidence: 99%
“…Apium graveolens belonging to the family Umbelliferae (English name Celery), is a herbaceous, biennial and branched stem medicinal plant wildly available in various countries, it is ordinarily cultured in the Europe area as a diet yield and it is also grown in Egyptian cities, regions of Kingdom of Saudi Arabia and Algeria 3 . Celery leaves contain flavonoids, tannins and saponins which have antibacterial effects, as the juice of its roots and leaves possess effective biochemical actions 4 . This extract has many medical activities like anticancer, antiinflammatory, anti-bacterial, anti-spasmodic, antihypercholesterolemic, anti-hepatotoxic and analgesic 5 with many types of research that record anti-inflammatory, antibacterial and antifungal effects of essential oil of celery 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…This plant can be used as a diuretic, for gland stimulation, bile, kidney stones, to regulate the intestines, to increase appetite, and as a prophylaxis for nervous agitation [21]. Other previous studies have also shown that celery has antimicrobial [22], antioxidant [23], cardioprotective [24],…”
Section: Counselling and Training On Making Snakehead Fish Nugget And...mentioning
confidence: 99%
“…The bulk of these herbs are utilized as raw plants, and herbs have been used to cure obesity all over the world in recent years. Efficacy and safety of medicinal plants in the treatment of obesity, dyslipidemia, and diabetes mellitus have been studied extensively (Genatrika et al, 2019). One of the annual or perennial plants that grows throughout Europe as well as the tropical and subtropical parts of Africa and Asia is celery (Apium graveolens L), a member of the Apiaceae family.…”
Section: Introductionmentioning
confidence: 99%